Mitigation of regional poverty in East Kalimantan: A village level panel data analysis - Hakim, Lukman; Bintariningtyas, Selfia; Juwita, Aulia Hapsari; Mulyanto, Mulyanto (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
Poverty is a specific problem so that programs that pay attention to spatial or demographic aspects are crucial to being able to create programs that are right on target in alleviating poverty. Apart from looking at demographic factors, we also analyze technological and institutional factors. This research aims to develop a Regional Poverty Mitigation Model in the province of East Kalimantan. This model is designed to provide a comprehensive framework for understanding and addressing poverty in the region. The focus of this research is specifically on the problem of poverty in the province of East Kalimantan. The data used in this study is the latest data from the 2021 Village Potential (Podes) of East Kalimantan province, which includes 1039 villages. The method used in this study is a quantitative analysis method using panel data which is then performed regression. The results show that geographical variables (regional areas and bordering the sea) have a negative and significant relationship to poverty in East Kalimantan, and technology has a positive and significant relationship to poverty in East Kalimantan. In addition, institutions (health and education) have a positive and significant relationship to poverty in East Kalimantan.